2014
DOI: 10.2478/mms-2014-0039
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of Low Frequency Noise of Infrared Photo-Detectors with Transimpedance Detection System

Abstract: The paper presents the method and results of low-frequency noise measurements of modern mid-wavelength infrared photodetectors. A type-II InAs/GaSb superlattice based detector with nBn barrier architecture is compared with a high operating temperature (HOT) heterojunction HgCdTe detector. All experiments were made in the range 1 Hz -10 kHz at various temperatures by using a transimpedance detection system, which is examined in detail. The power spectral density of the nBn's dark current noise includes Lorentzi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…has been published elsewhere [9]. It was shown that the power spectral density (PSD) of the system noise…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…has been published elsewhere [9]. It was shown that the power spectral density (PSD) of the system noise…”
Section: Resultsmentioning
confidence: 99%
“…The referenced Hg 1−x Cd x Te MWIR detectors were grown by metal organic chemical vapor deposition in VIGO System, S. A. laboratories. The architecture and fabrication details of the detectors have already been described [9]- [11]. The devices with different bandgap of the absorber related to Cd content x = 0.247 (specimen #1) and x = 0.321 (specimen #3) were used in the investigations.…”
Section: Samplesmentioning
confidence: 99%
“…The setup used for low-frequency noise measurements and the small-signal equivalent circuit of a photodiode were described in Ref. [25]. In Figure 4a, power spectral densities measured at T = 200 K for the low and high bias voltages are shown.…”
Section: Noise Characteristicsmentioning
confidence: 99%
“…In most cases, LFNMs have employed general-purpose commercial instrumentation to target relatively high-impedance DUTs. However, the fast progress in semiconductors and new materials process technologies often results in the need to develop dedicated instrumentation and new methodologies for noise measurement and analysis [11][12][13]. Obtaining reliable noise characterization is especially challenging in the case of low-resistance DUTs (impedances below 10 Ω), and in these cases it is necessary to resort to a dedicated amplifier design and/or to the application of cross-correlation methods [14,15].…”
Section: Introductionmentioning
confidence: 99%